Scaled citizen science participatory variety selection provides socially inclusive feedback to the cassava breeding in Nigeria and opens the way to empower women and men crop users within the breeding process - Teeken, Béla; Occelli, Martina; Sousa, Kaue de; Heerwaarden, Joost van; Madu, Tessy; Onwuka, Samuel; Etten, Jacob van; Nwanze-Olaosebikan, Olamide; Edughaen, Gospel; Owoade, Durodola; Agbona, Afolabi; Tufan, Hale Ann; et al. (International Institute of Tropical Agriculture, 2023)
This study investigated varietal and trait preferences of cassava farmers and the processors in their households and how they differed by value chain actor, gender, region and typologies of users. New breeding lines and popular varieties among users were evaluated with 320 farmers across Nigeria using the tricot citizen science method. Varieties were evaluated at 11 timepoints from planting to processed food products. Agronomic evaluation was done with the farmers. Processing evaluation was done with experienced processors: often a woman in the farmer’s household. RHoMIS and 1,000 minds surveys provided further characterization of farmers’ households. Next to root-yield-related traits, agronomic traits like weed competitiveness, processing and food-product quality traits such as food color and texture correlated strongly with the farmers’ households’ final variety choice. From planting to food processing, variety and trait preferences changed differently for several intersections of social segments. For instance, the intersection “women farmers that also did the processing” showed a consistent preference for specific varieties and traits during the postharvest processing stage. Women’s expertise is crucial to consult to identify varieties and traits that drive the efficiency and profitability of the value chain as a whole, and for women in particular. Doing consultation that is deliberatively rather than performative/participatory to crop users provides key information for breeding. Such approaches can be integrated in breeding practices by using tricot for on-farm testing within the variety release procedure. Working with women and men users as citizen scientists institutionally opens the way to emancipate users within the breeding process.